2014
DOI: 10.3345/kjp.2014.57.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of respiratory viral infection in children hospitalized for acute lower respiratory tract diseases, and association of rhinovirus and influenza virus with asthma exacerbations

Abstract: PurposeIn this study, we aimed to investigate the prevalence of year-round respiratory viral infection in children with lower respiratory tract infection (LRTI) and the relationship between respiratory viral infection and allergen sensitization in exacerbating asthma.MethodsWe investigated the sources for acute LRTIs in children admitted to our hospital from May 2010 to April 2011. The 6 most common respiratory viruses were isolated from nasopharyngeal aspirate using multiplex reverse transcription-polymerase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
45
2
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 31 publications
7
45
2
6
Order By: Relevance
“…This rate is relatively high compared to those obtained in several other studies [4,18,27,31,32] even if others studies had concluded that influenza viruses are more likely to be detected in under 5-year-old patients, with an incidence of 9.4-9.6% in the last 2 years [33][34][35]. Moreover, Van Woensel, et al [36] argued that infants and young children have a 12-fold increased risk of admission to hospital for respiratory tract infection caused by influenza virus compared with children aged 5-17 years.…”
Section: Discussioncontrasting
confidence: 42%
“…This rate is relatively high compared to those obtained in several other studies [4,18,27,31,32] even if others studies had concluded that influenza viruses are more likely to be detected in under 5-year-old patients, with an incidence of 9.4-9.6% in the last 2 years [33][34][35]. Moreover, Van Woensel, et al [36] argued that infants and young children have a 12-fold increased risk of admission to hospital for respiratory tract infection caused by influenza virus compared with children aged 5-17 years.…”
Section: Discussioncontrasting
confidence: 42%
“…It has been reported that infants with highest IgE-anti-RSV responses had more wheezing episodes than infants who did not have IgE anti-RSV responses [21]. However, the results of our current study are consistent with previous reports that found a possible relationship between RSV-specific IgE response at the time of infection and subsequent wheezing [22], and that RSV infection is frequently observed in patients with acute bronchiolitis [23]. But, it should be mentioned, due to our cross-sectional study design, we were unable to determine whether the above differences in subjects with asthma were due to recurrent or prolonged infections.…”
Section: Discussionsupporting
confidence: 82%
“…In a study conducted in our country in which 27 cases of AV-related respiratory infection were examined, it was reported that the patients were mostly aged 4 years and older (22). In another study, it was reported that AV infections were found at older ages compared to RSV infections (mean age, 41 months, 23 months) (23). Although human metapneumovirus and HBoV may be observed in any age group, studies have shown that they mostly affect younger children (24,25).…”
Section: Discussionmentioning
confidence: 99%